2020
DOI: 10.3897/folmed.62.e46678
|View full text |Cite
|
Sign up to set email alerts
|

Normal Reference Ranges of Optical Coherence Tomography Parameters in Children

Abstract: Aim: To measure the macular thickness, macular volume and peripapillary retinal nerve fiber layer (RNFL) in healthy Caucasian chil­dren using spectral domain optical coherence tomography (SDOCT) and analyze the correlation of these values with age, refraction, and biometric measurements. Materials and methods: In this cross-sectional study, we recruited 270 healthy children (150 female and 120 male) aged 6 to 17 years with no ocular abnormalities. All children underwent a detailed eye examina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
5
3
0
Order By: Relevance
“…Our study did not find statistically significant differences between male and female RNFL thickness, in accordance with an important number of studies regardless of the technology that was used [ 17 , 18 , 21 , 24 , 25 , 30 , 33 , 34 , 38 , 39 , 40 , 41 , 42 , 43 ]. Turk et al found a significant difference between female and male children in terms of RNFL only in the temporal inferior segment, without any significant difference in the other RNFL parameters [ 22 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our study did not find statistically significant differences between male and female RNFL thickness, in accordance with an important number of studies regardless of the technology that was used [ 17 , 18 , 21 , 24 , 25 , 30 , 33 , 34 , 38 , 39 , 40 , 41 , 42 , 43 ]. Turk et al found a significant difference between female and male children in terms of RNFL only in the temporal inferior segment, without any significant difference in the other RNFL parameters [ 22 ].…”
Section: Discussionsupporting
confidence: 91%
“…In comparison with Spectralis, the Copernicus technology, REVO80, measured significantly higher mean global RNFL values, in accordance with the single literature result performed on the same age group and same conditions [ 30 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…All macular quadrants and the macular volume a significant positive correlation with results are consistent with the state of research, [25][26][27][28] although contrary results also been These findings could lead to the assumption that macular development is a long process that is not completed in early childhood. During the first 5 years of life, a logarithmic increase in the photoreceptor layer and a decrease in the ganglion cells and the inner nuclear layer occurs.…”
Section: Agesupporting
confidence: 74%
“…We compared the retinal thickness in nasal and temporal sectors between XLAS patients and the control group. Since the range of variation of the retinal thickness was large in different papers [20][21][22] , the TTI was useful to address the relative thinning of the temporal quadrant. Therefore, we use the TTI as our main result.…”
Section: Retinal Thinning In Alport Syndromementioning
confidence: 99%